Cyberbullying victimization and symptoms of depression and anxiety among Chinese adolescents: Examining hopelessness as a mediator and self-compassion as a moderator. (September 2018) - Chu, Xiao-Wei; Fan, Cui-Ying; Liu, Qing-Qi; Zhou, Zong-Kui
Abstract: Cyberbullying victimization has been identified as a significant vulnerability factor in the development of adolescents' depression and anxiety. However, little is known about the underlying processes that may mediate or moderate these relationships. The present study examined hopelessness as a mediator and self-compassion as a moderator in the relations between cyberbullying victimization and symptoms of depression and anxiety. The sample consisted of 489 Chinese early adolescents aged from 11 to 15 years ( M  = 12.67, SD  = 0.75; 43.6% girls) who completed measures of cyberbullying victimization, hopelessness, self-compassion, depression, and anxiety. Bias-corrected bootstrap method was employed to test the proposed moderated mediation models. Results indicated that after controlling for participants' gender and age, hopelessness partially mediated the relationships between cyberbullying victimization and depression as well as anxiety. The direct effects of cyberbullying victimization on depression and anxiety, and the mediation effects of hopelessness were moderated by self-compassion. Specifically, these effects were much stronger for adolescents with lower self-compassion. The present study can extend our knowledge about how, when, and when of how cyberbullying victimization is related to depression and anxiety. Limitations and practical implications of this study are further discussed. Highlights: Cyberbullying victimization (CV) was positively related to depression/anxiety. Hopelessness mediated the relations between CV and depression/anxiety. Self-compassion moderated the direct relations between CV and depression/anxiety. Self-compassion moderated the mediating effects of hopelessness.